عروض مختصرة - ملكاوي فتحي حسن (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2002)
What Did the Biblical Writers Know & When Did They Know? What Archeology can tell us about the Reality of Ancient Israel? William G. Dever. Michigan: Wm. B. Eerdmans, 2001, 133 pages. The Bible Unearthed: Archaeology’s New Vision of Ancient Israel and The Origin of Its Sacred Texts. Israel Finkelstein and Neil Asher Silberman. New York: The Free Press, 2001, 400 pages. Blinded By the Right: The Conscience of an Ex-Conservative. By David Brock. New York: Crown Publishers, 2002, 336 pages. Many Globalizations: Cultural Diversity in the Contemporary World. Edited By Peter Berger and Samuel Huntington. New York: Oxford University Press, 2002, 274 pages. Who Owns History: Rethinking the Past in a Changing World. Eric Foner. New York: Hill and Wang, 2002, 234 pages Paths from Science Towards God: The End of all our Exploring. Arthur Peacock. England: One world Publications, 2001, 198 pages. The Death of the West: How Mass Immigration, Depopulation and a Dying Faith Are Killing our Culture and Country. By Patrick J. Buchanan. St. Martin’s Press Inc., 320 pages. The Qur’anic Phenomenon: An Essay of Theory on the Qu’ran. Malik Bennabi. Translated and Annotated by Mohamed El-Taher El-Mesawi: Malaysia: Islamic Book Trust, 2001, 298 pages. What went wrong? Western Impact and Middle Eastern Response. Bernard Lewis. New York: Oxford University Press, Inc., 2001, 192 pages. The Muslim Jesus: Saying and Stories in Islamic Literature. Edited and Translated By Tarif Khalidi. Cambridge: Harvard University Press, 2001, 245 pages. The Paradox of American Power: Why the World’s Only Superpower Can’t Go It Alone. Joseph S. Nye, Jr.. New York: Oxford University Press, Inc., 2002, 240 pages. Unholy War: The Vatican’s Role in the Rise of Modern Anti-Semitism. David I. Kertzer. London: Macmillan, 2002,355 pages. Our Postmodern Future: Consequences of the Biotechnology Revolution. By Francis Fukuyama. New York: Farrar, Straus and Giroux, 2002, 256 pages. Western Political Science in a Non-Western Context: Theories of Comparative Politics in the Arab Academia. Nasr M. Arif. Lanham, MD: University Press of America, Inc., 2001, 105 pages. The Hinges of Battle: How Chance and Incompetence Have Changed the Face of History. Eric Durschmied. London: Hodder and Stoughton, 2002, 438 pages. من أعلام الحركة الإسلامية. المستشار عبد الله العقيل. الكويت: مكتبة المنار الإسلامية، 2000م، 716 صفحة. نظرية المعرفة في القرآن الكريم وتضميناتها التربوية. د. أحمد حسين الدغشي. هيرندن فيرجينيا: المعهد العالمي للفكر الإسلامي، ودمشق: دار الفكر، 2002م، 472 صفحة. العقل الأخلاقي العربي: دراسة تحليلية نقدية لنظم القيم في الثقافة العربية. محمد عابد الجابري. (سلسلة نقد العقل العربي 4.) الدار البيضاء: دار النشر المغربية، 2001م، 640 صفحة. نقد العقل العربي: وحدة العقل العربي الإسلامي. جورج طرابيشي. بيروت: دار الساقي، 2002م، 408 صفحة. السلطة السياسية في الفكر الإسلامي: محمد رشيد رضا نموذجاً. محمد سليمان أبو رمان. عمان: دار البيارق، 2002م، 295 صفحة. للحصول على كامل المقالة مجانا يرجى النّقر على ملف ال PDF في اعلى يمين الصفحة.